Correlation Between Traumatic Skin and Subcutaneous Injuries and the Severity of Polytrauma Injury - Klempka, Anna; Fischer, Christian; Kauczor, Hans-Ulrich; Weber, Marc-André (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2020)
Purpose To examine the relationship between superficial lesions (such as bruises, hematomas, deep abrasions, and soft tissue emphysema) and internal post-traumatic injuries, assessed using whole-body computed tomography (WBCT), and to determine if these are valid markers for internal injuries.Methods and Materials 250 patients who underwent WBCT emergency scans for suspected polytrauma were retrospectively analyzed after institutional review board approval of the study. The scans were carried out on patients who met the criteria for standard operating procedures for WBCT emergency scans. WBCT covering the entire head, neck, chest, and abdomen (including pelvis and proximal lower extremities) and at least one phase with intravenous contrast agent were included in the study. Initial analyses of immediate WBCT scans was carried out by a consultant radiologist and a radiological resident. The first reading focused on internal damage that needed immediate therapy. The second reading focused on a detailed analysis of the skin and subcutaneous tissue and their relation to internal injuries without the time pressure of an emergency setting, carried out by another experienced radiologist. All skin lesions and the degree of penetration and a comparison between the two readings were reported in tables.Results Superficial lesion of the chest was detected in 19 patients, 17 of them had an internal injury of the thorax while only two patients, with hematoma of the chest wall, had no internal injuries. Skin and subcutaneous lesions of the chest had the strongest association with an internal injury. Skin lesions of the abdominal wall were observed in 30 patients. In only 11 cases, these lesions were correlated with internal injuries, such as fractures or active bleeding. 52 skin and subgaleal lesions of the scalp were observed. In 20 of these patients, an intracranial or internal injury was detected. In 3 patients, skin abrasions of the neck were present and in only one of them, this finding was associated with an internal injury.Conclusion Trauma patients whose history and clinical presentation meet the standard operating procedures for WBCT emergency scans and who present with a cutaneous lesion, especially at the neurocranium or chest wall, should be observed for internal injuries by WBCT.Key Points: Citation Format
Keywords: abdominal wall; thorax; thorax wall; head injury